2020
DOI: 10.1002/mds.28408
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Hospitalization and Death for COVID‐19 in People with Parkinson's Disease or Parkinsonism

Abstract: Background The risk of COVID‐19 and related death in people with Parkinson's disease or parkinsonism is uncertain. The aim of the study was to assess the risk of hospitalization for COVID‐19 and death in a cohort of patients with Parkinson's disease or parkinsonism compared with a control population cohort, during the epidemic bout (March–May 2020) in Bologna, northern Italy. Methods Participants of the ParkLink study with the clinical diagnosis of Parkinson's disease o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(80 citation statements)
references
References 47 publications
6
69
1
Order By: Relevance
“…Thus far, several studies have suggested a relationship between COVID-19 and neurodegenerative disorders. An early report [ 19 ] this year showed that a dementia diagnosis was associated with the largest increase in the risk of COVID-19 in the UK Biobank based on a smaller cohort of 507 COVID-19-positive patients from England aged 65 and older. Dementia has also been found to increase the risk of in-hospital mortality in a large cross-sectional analysis of 20,133 patients already hospitalised for COVID-19 in the UK [ 13 ], a finding later replicated by two cohort, retrospective studies [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus far, several studies have suggested a relationship between COVID-19 and neurodegenerative disorders. An early report [ 19 ] this year showed that a dementia diagnosis was associated with the largest increase in the risk of COVID-19 in the UK Biobank based on a smaller cohort of 507 COVID-19-positive patients from England aged 65 and older. Dementia has also been found to increase the risk of in-hospital mortality in a large cross-sectional analysis of 20,133 patients already hospitalised for COVID-19 in the UK [ 13 ], a finding later replicated by two cohort, retrospective studies [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our cohort included 157 participants with parkinsonism, of whom 142 were diagnosed with PD. To account for potential differences between parkinsonism and PD in the context of COVID-19-related vulnerability [ 19 ], we built 2 separate models—one with individuals diagnosed with parkinsonism and one with PD patients only. Information on all covariates was obtained from primary care records provided by the UK Biobank.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In December 2019, the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) or Covid-19, causing a pneumonia-like illness, emerged in China and spread quickly all around the world and now is an ongoing pandemic [1]. The effect of the neurological disorder as a risk factor for Covid- 19 infection is yet to be fully understood, and its impact on clinical features of these diseases need to be well characterized [2]. Parkinson's disease (PD) is one of the most common neurodegenerative disorders of the central nervous system, with an increased prevalence by aging [3].…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 has been widely studied in people with Parkinson's disease (PwPD)[ 1 ], but besides a study including only nine people with multiple system atrophy (PwMSA) in a cohort of mostly vascular parkinsonism cases [ 2 ], information is lacking on COVID-19 outcomes in PwMSA.…”
mentioning
confidence: 99%